Assessing reaeration rate equations for modelling dissolved oxygen of Pusu river in Malaysia - Mamun, Abdullah Al; Nuruzzaman, M.; Salleh, M.N. (Akademi Sains Malaysia, 2023)
Many authors reported high variability in the prediction of reaeration rates by various equations, leading to uncertainty in the estimation of the reaeration rate for a river. Due to this uncertainty, it is essential to identify a suitable equation to predict the dissolved oxygen (DO) concentration of the river in concern. Pusu River in Malaysia receives sewage discharges and suffers from land-clearing activities and stormwater-related pollution. Pusu River is a small river, but highly important in terms of demography and geographic location. As such, it is required to identify a suitable reaeration rate equation for predicting its DO concentration, which indicates the overall health of a river. The purpose of this study is to assess the suitability of reaeration rate equations to predict Dissolved Oxygen (DO) concentrations of the Pusu River. The water quality analysis simulation program (WASP) model was employed to model the DO of the Pusu River. Reaeration rates calculated from the available 31 equations were given input in the model, and errors in prediction were calculated in terms of Root Mean Square (RMS) error and R2 for every equation. It was revealed that Neguluscu and Rojanski (1969) equation using depth and velocity as the variables performed best among all the equations. It produced a minimum RMS error of 0.17 and 0.09 mg/L in calibration and validation data, respectively. R2 values for predicted-observed plots were 0.98 and 0.97 in these two data sets using the equation. Based on overall Performance Indicator Values (PIVs), reaeration rate equations with depth and velocity as the variables performed better than the other equations with more variables for Pusu River. This study provided important information to accurately model the DO of the Pusu River for future simulation of different scenarios